PERAN KODE ETIK PROFESI DALAM MENINGKATKAN PROFESIONALISME PUSTAKAWAN - -, Rahmat (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
Library Managers or commonly referred to as "Librarians" are officially recognised as professional positions or within the government as functional positions. MENPAN and RB Regulation No. 9 of 2014 concerning the Functional Position of Librarian and its Credit Score, where the main consideration "that in order to meet the demands of career development and increase the professionalism of Librarians, it is necessary to reorganise the MENPAN Decree No. PAN/12 / 2002 concerning the Functional Position of Librarian and its Credit Score". The ethical symbols of librarians include mutual respect, mutual honour, and mutual assistance. The research method used in this study is qualitative. In this case, researchers interpret and explain the data taken from various related literature. The literature used are journals, websites, and google so that the data collected is then analysed descriptively in accordance with the object of research so as to get answers to problems in detail. This research focuses on the discussion of ethics that librarians must have in order to increase interest in visiting the library. The main task of librarians is to collect, compile and organise information that will be delivered to users or the entire community. But, in a dynamic environment, a librarian has to deal with ethical issues, not only in terms of service, but also in terms of professionalism and technical education for self-satisfaction and prospective operators. A code of conduct known as the Librarian's Code of Ethics governs ethical issues in the field of librarianship. As members of the profession, librarians are obliged to abide by the code of ethics. Librarians have the responsibility to apply the code of ethics as standards and guidelines for the needs of the profession, professional organisations, libraries and users. For this reason, librarians must be able to act professionally so that the library can improve the quality of the library while achieving common goals..